2022
DOI: 10.1101/2022.05.22.22275422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 NSP3, NSP4 and NSP6 mutations and Epistasis during the pandemic in the world: Evolutionary Trends and Natural Selections in Six Continents

Abstract: Background: The Coronavirus 2019 (COVID-19) was named by the World Health Organization (WHO) due to its rapid transmittable potential and high mortality rate. Based on the critical role of None Structural Proteins (NSP), NSP3, NSP4, and NSP6 in COVID-19, this study attempts to investigate the superior natural selection mutations and Epistasis among these none structural proteins. Methods: Approximately 6.5 million SARS-CoV-2 protein sequences of each NSP3, NSP4, and NSP6 nonstructural protein were analyzed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…NSP3 with NSP4 rearrange host-derived membranes and plays a role in the replication of SARS-CoV [41]. A total of 32.8% of NSP4 was conserved and presented 40 mutations, including T492I (6%), L264F (1.3%), and T327I (1.2%) that were reported in previous studies [35, 42, 43].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…NSP3 with NSP4 rearrange host-derived membranes and plays a role in the replication of SARS-CoV [41]. A total of 32.8% of NSP4 was conserved and presented 40 mutations, including T492I (6%), L264F (1.3%), and T327I (1.2%) that were reported in previous studies [35, 42, 43].…”
Section: Resultsmentioning
confidence: 94%
“…The transcriptome analysis of Sun et al demonstrated that the L37F mutant failed to trigger pyroptosis and the downstream inflammasome pathway [51]. In our recent study, we showed that the T77A mutation is one of the top mutations globally, with a frequency of 69.8% [43].…”
Section: Resultsmentioning
confidence: 99%
“…However, The PLpro central catalytic residues were highly conserved [ 82 ]. Based on fooladinezhad, results, in North America NSP3 data, 41.47% of aa showed more than four mutations in their sequence [ 22 ]. The region corresponding to the C-terminal domain of SARS-CoV NSP3 was found to be significantly less mutated likely due to its vital role in inducing the formation of [ 2 ] double-membrane vesicles [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that Omicron could have emerged due to epistatic interactions that may allow for the emergence of mutations not seen in other variants or that are very rare [57][58][59] . The low intra-host evolution for SARS-CoV-2 and relatively limited transmission bottleneck 60,61 suggest that Omicron may have evolved in chronically infected patients where the virus can cross through fitness valleys that may not be possible in an acute infection 57 .…”
Section: Discussionmentioning
confidence: 99%